O teorema de Dirichlet: primos em progressão aritmética - Silva Júnior, José Carlos (2017)
In this work we will present some basic results of the number theory with the objective of exploring the study of primes in arithmetic progressions whose commom di erence and rst term are coprime. We will present proofs of some particular cases of Dirichlet's theorem on PA primes, in addition to presenting some older results and other recent ndings about how the primes distribute themselves in certain arithmetic progressions.